Family Resources Management in Cibanteng Village, Ciampea, Bogor District - Risda Rizkillah; Megawati Simanjuntak (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Family resources are something that must be adequately managed that can be used optimally to achieve family goals. This study aims to analyze the process of family resource management include planning, task control, communication structure, decision making, and time allocation. This study applies a cross-sectional design. The location of data collection was conducted in the Cibanteng Village area, Ciampea District, Bogor Regency, West Java. The population in this study were families living in Cibanteng Village, Ciampea District. The sampling unit in this study is the family with the respondent is a wife. The sampling was taken purposively and obtained samples of 40 families. The results of the study showed that in the planning implementation, the majority of families never wrote their life plans in the family. The majority of mothers control domestic problems such as housework, children's education, and childcare. The structure of communication and decision making in the family carried out by the majority family only involves husband and wife. The higher the productive time allocated by the wife, the smaller the allocation of leisure time and household time. Also, the higher the social time allocation devoted by the wife, the smaller the allocation of household time and personal time allocation.